2015
DOI: 10.1371/journal.pone.0142164
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis and Lowered Serum Lipopolysaccharide-Binding Protein in Parkinson’s Disease

Abstract: BackgroundThe intestine is one of the first affected organs in Parkinson’s disease (PD). PD subjects show abnormal staining for Escherichia coli and α-synuclein in the colon.MethodsWe recruited 52 PD patients and 36 healthy cohabitants. We measured serum markers and quantified the numbers of 19 fecal bacterial groups/genera/species by quantitative RT-PCR of 16S or 23S rRNA. Although the six most predominant bacterial groups/genera/species covered on average 71.3% of total intestinal bacteria, our analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
361
8
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(421 citation statements)
references
References 50 publications
24
361
8
3
Order By: Relevance
“…These include depletions in members of family Lachnospiraceae and Ruminococceae in recipient mice, a notable finding as these same genera are significantly reduced in fecal samples directly from PD patients (Keshavarzian et al, 2015). Conversely, the gut microbiomes in human subjects with PD contain an increased abundance of Proteobacteria (Hasegawa et al, 2015; Keshavarzian et al, 2015; Scheperjans et al, 2015; Unger et al, 2016), remarkably similar to our results in mice. Whether these specific microbes play a role in disease processes remains unknown.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These include depletions in members of family Lachnospiraceae and Ruminococceae in recipient mice, a notable finding as these same genera are significantly reduced in fecal samples directly from PD patients (Keshavarzian et al, 2015). Conversely, the gut microbiomes in human subjects with PD contain an increased abundance of Proteobacteria (Hasegawa et al, 2015; Keshavarzian et al, 2015; Scheperjans et al, 2015; Unger et al, 2016), remarkably similar to our results in mice. Whether these specific microbes play a role in disease processes remains unknown.…”
Section: Discussionsupporting
confidence: 88%
“…Given recent evidence that PD patients display altered microbiomes (Hasegawa et al, 2015; Keshavarzian et al, 2015; Scheperjans et al, 2015), we sought to determine whether human gut microbes affect disease outcomes when transferred into GF mice. We collected fecal samples from 6 human subjects diagnosed with PD, as well as 6 matched healthy controls (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…76,85,[96][97][98] Several studies have also indicated abnormalities in the tight junctions of intestine without complete damage in the mucosa, but characterized by a decrease in the barrier promoting protein levels and disruptions of tight junction networks, 76,92,93 thus showing a phenotype consistent with low-grade inflammation. 72 The penetration of E. coli into the intestinal mucosa seems to be expressed more frequently in PD patients as compared to controls, and correlate with increased intestinal permeability and oxidative stress and increased enteric a-synuclein levels.…”
Section: Altered Intestinal Barrier Functionmentioning
confidence: 99%
“…Recently, it has been shown that individuals with PD have an altered gut microbial composition (25)(26)(27)(28), raising the possibility that gut microbes affect PD pathogenesis. In a mouse model of PD, gut microbiota promoted α-synuclein aggregation and the development of motor disturbances (29).…”
Section: Introductionmentioning
confidence: 99%